2018
DOI: 10.1016/j.ijporl.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare and psychosocial experiences of individuals with craniofacial microsomia: Patient and caregivers perspectives

Abstract: The survey results on the healthcare and psychosocial experiences from birth through adulthood of individuals with CFM reinforce the need for ongoing psychological assessment and intervention. Healthcare provision could be improved through establishing diagnostic criteria and standardized treatment guidelines, as well as continued investigation of CFM etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 20 publications
3
19
0
2
Order By: Relevance
“…In a study of young children with microtia (Johns et al, 2017), teasing was reported to begin between the ages of 2 to 5 years and to increase with age, with all the children in this sample reported having been teased by age 6. Similar early teasing patterns were reported by Luquetti et al (2018) in a larger sample of children with CFM.…”
Section: Introductionsupporting
confidence: 85%
“…In a study of young children with microtia (Johns et al, 2017), teasing was reported to begin between the ages of 2 to 5 years and to increase with age, with all the children in this sample reported having been teased by age 6. Similar early teasing patterns were reported by Luquetti et al (2018) in a larger sample of children with CFM.…”
Section: Introductionsupporting
confidence: 85%
“…CFM is estimated to occur in 1 in 3,500 to 5,600 live births ( Poswillo, 1988 ) and can result in surgeries to restore craniofacial form and function, such as for the ear, eye, mandible, facial nerve, and orbit ( Birgfeld & Heike, 2012 ). Students with CFM can receive rehabilitation services, including occupational and speech therapies ( Luquetti et al, 2018 ; Speltz et al, 2017 ), and can experience reduced quality of life relative to unaffected peers, as indicated by caregiver-reported difficulties in physical, social, and school functioning ( Khetani et al, 2013 ) that may hinder their school participation. These functional difficulties include lower verbal processing skills, including vocabulary, reading, and writing ( Speltz et al, 2017 ), and behavioral–social adjustment ( Wallace et al, 2018 ), as well as greater social concerns ( Johns et al, 2018 ; Khetani et al, 2013 ; Luquetti et al, 2018 ) and stigma because of their appearance ( Hamilton et al, 2018 ; Luquetti et al, 2018 ).…”
mentioning
confidence: 99%
“…These study questions expand on their reports of overall healthcare and psychosocial experiences. 23 The nuanced perspective of patients and their families reflects the growing recognition of the importance of including patient reported outcome measures and integrating their feedback in ongoing quality improvement in clinical practice. 24…”
Section: Introductionmentioning
confidence: 99%